Fasciola gigantica: Histology of the digestive tract and the expression of cathepsin L - Krai Meemon (2018)
The digestive tract of Fasciola gigantica is composed of the oral sucker, buccal tube, pharynx, esophagus, and caecum. The tegumental-type epithelium lines the first four parts of the digestive tract while the caecal-type epithelium lines the remaining parts from the caecal bifurcation. The caecal-epithelial cells are classified into 3 types according to their staining properties and ultrastructural characteristics, as related to the amount of food contents in the caecal lumen. All caecal-type epithelial cells synthesize and secrete cathepsin L, a major group of enzymes in the digestive tract, as detected by in situ hybridization and immunolocalization. Moreover, the secreted cathepsin L is also adsorbed on the outer surface of the tegument and the glycocalyx coating of the surface of the tegument, whereas the tegumental cells and tegumental syncytium covering the parasite's body and lining the proximal part of the digestive tract exhibit no in situ hybridization signal and immunostaining for cathepsin L. © 2010 Elsevier Inc.